2018
DOI: 10.1002/da.22730
|View full text |Cite
|
Sign up to set email alerts
|

Digital phenotyping of suicidal thoughts

Abstract: Suicidal thinking has historically been studied as a homogeneous construct, but using newly available monitoring technology we discovered five profiles of suicidal thinking. Key questions for future research include how these phenotypes prospectively relate to future suicidal behaviors, and whether they represent remain stable or trait-like over longer periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 29 publications
8
127
0
2
Order By: Relevance
“…change scores), evaluating different contextual factors or mood states as well as the impact of treatment (attendance, adherence, type), or, as found in this study, by examining synergistic effects of risk indicators. A focus on distinct phenotypes of SI, accounting for its intensity and variability, in real‐time (Kleiman et al., ) could offer another promising approach to short‐term risk identification. Research employing frequent assessments across different populations as well as settings is needed to help address these research questions and ultimately help identify meaningful targets of intervention for individuals at elevated suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…change scores), evaluating different contextual factors or mood states as well as the impact of treatment (attendance, adherence, type), or, as found in this study, by examining synergistic effects of risk indicators. A focus on distinct phenotypes of SI, accounting for its intensity and variability, in real‐time (Kleiman et al., ) could offer another promising approach to short‐term risk identification. Research employing frequent assessments across different populations as well as settings is needed to help address these research questions and ultimately help identify meaningful targets of intervention for individuals at elevated suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…There are now new efforts to develop apps that will offer users help in emergencies. Recent research on real-time smartphone monitoring of suicidal ideation in those recently discharged from inpatient psychiatric units highlights the potential of apps to offer actionable insights on the real-time and personalised risk factors for suicidal ideation 43. Some start-ups are also exploring how peer crowd sourcing-based smartphone apps may help direct users in need to immediate help via suicide hotlines 44…”
Section: Improving App Engagementmentioning
confidence: 99%
“…Building upon these findings, future studies may want to evaluate different qualitative aspects relating to NSSI thoughts [i.e., intensity, duration, controllability; (71,78)], and explore whether meaningful patterns can be identified in relationship to risk for NSSI behavior. In suicide research, for instance, scholars have identified different phenotypes of suicidal thinking, and were able to associate a thought profile characterized by severe persistent suicidal thoughts to a recent suicide attempt (79).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%